PENGEMBANGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA MATERI IPS KELAS V SEKOLAH DASAR - Didin Tahajudin; Maulina Rahayu; Fauzi Fadliansyah (Amal Insani Foundation, 2023)
This study aims to produce a learning product in the form of kinemaster-based audio-visual media as teaching material for fifth grade students in social studies on the subject of struggle against invaders to improve student learning outcomes. The method used is the development research (R&D) method, up to the testing stage of the effectiveness of the products that have been developed. To determine the feasibility of material and media, validity tests have been carried out by material and media experts. The results of product validity by two experts obtained very feasible category. Material experts obtained a value of 88.6% and media experts obtained a value of 87.5%. To find out the effectiveness of the media on subject matter, a field trial was carried out at SD Negeri Montor 1. The results of the field trial for student responses to the media obtained 95.6% in the very feasible category and student learning outcomes obtained an average score of 83.3%, the test results of the teacher's response to the media obtained 89.2%. Based on the results of the analysis of two experts and trials on students and teachers, the audio-visual media meets the criteria to be used as a learning medium for Social Sciences (IPS).